Corporate responsibility in the UK construction industry: a study of activities and reporting - Brown, James Daniel (2012)
Corporate Responsibility (CR) defines the process of self-regulation, whereby an organisation seeks to measure and improve its performance related to the social, environmental and economic expectations placed upon it by society.